Penerapan Model Discovery Learning Berbantuan Media Pictorial Timeline untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa - Naili Fauziah; Fajri Ismail (Bahasa Indonesia, Bahasa English, 2019)
This study aims to determine the use of the Discovery Learning model assisted by the Pictorial Timeline media in improving students' chronological thinking skills on Islamic Cultural History subjects. This type of research is experimental research with a quantitative approach. The design used is the non equivalent control group design. The population in this study were all eighth grade students of MTsN Padang Panjang and the sampling technique was purposive sampling. The sample in this study was class VIII B with 33 students as the control class, class VIII D totaling 33 students as experimental class 1 and class VIII E totaling 33 students as experimental class 2. The research design used was quasi-experimental. The instruments used in this study were chronological thinking skills test questions in the form of multiple choice. Data analysis using one-way ANAVA test. The results of this study are: the average posttest results of students who use discovery learning models assisted by pictorial timeline media are higher than students who use discovery learning models without the help of pictorial timeline media, and the average posttest results of students who use discovery learning models without the help of pictorial timeline media are more higher than students who use conventional learning models that is 84.18> 74.88> 66.76 This study shows that there are differences in the average between the sample classes. In accordance with the ANAVA test that obtained Fcount ≥ F table which is 65.432 ≥ 3.09 so H0 was rejected.